2010
DOI: 10.1063/1.3360826
|View full text |Cite
|
Sign up to set email alerts
|

A sensitive near-field microscope for thermal radiation

Abstract: A scattering-type scanning near-field optical microscope in long-wavelength infrared (LWIR) region is developed by using an extremely sensitive detector, called the charge-sensitive infrared phototransistor. A tungsten probe attached to a quartz tuning fork is controlled in shear-force mode. Evanescent wave at a sample surface is periodically scattered by slowly (2 Hz) modulating the probe in the direction normal to the sample surface. Near-field microscopy of thermal LWIR radiation from room-temperature Au/Ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(27 citation statements)
references
References 21 publications
0
27
0
Order By: Relevance
“…They concluded that the contribution to the EM-LDOS is dominated by SPhP on SiC at d = 200 nm but by SPP on gold at a larger distance of 3 µm, demonstrating spatial coherence effects of near-field thermal emission from thermally excited surface plasmons without any external illumination. Kajihara et al [153] demonstrated a spatial resolution of 300 nm by measuring thermal emission from gold plasmonic gratings. A charge-sensitive infrared phototransistor was used for probing the scattered long-wavelength infrared radiation near 15 µm wavelength [153].…”
Section: Near-field Imaging Local Heating or Cooling And Nanomanufamentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that the contribution to the EM-LDOS is dominated by SPhP on SiC at d = 200 nm but by SPP on gold at a larger distance of 3 µm, demonstrating spatial coherence effects of near-field thermal emission from thermally excited surface plasmons without any external illumination. Kajihara et al [153] demonstrated a spatial resolution of 300 nm by measuring thermal emission from gold plasmonic gratings. A charge-sensitive infrared phototransistor was used for probing the scattered long-wavelength infrared radiation near 15 µm wavelength [153].…”
Section: Near-field Imaging Local Heating or Cooling And Nanomanufamentioning
confidence: 99%
“…Kajihara et al [153] demonstrated a spatial resolution of 300 nm by measuring thermal emission from gold plasmonic gratings. A charge-sensitive infrared phototransistor was used for probing the scattered long-wavelength infrared radiation near 15 µm wavelength [153]. Similarly, Kittel et al [154] showed the near-field thermal imaging from nanostructured surfaces by measuring the near-field LDOS of thermally excited electromagnetic waves at nanometer distances from the sample surface.…”
Section: Near-field Imaging Local Heating or Cooling And Nanomanufamentioning
confidence: 99%
“…The [27] value of D * for CSIP is much higher than 300K-photonnoise limited performance, which will meet the requirements for high-resolution real-time passive imaging of RT small objects, e.g., living bio-cells. Recently CSIPs have been applied to the construction of a highly sensitive passive microscope [31,32].…”
Section: Device Performancementioning
confidence: 99%
“…16,[22][23][24] At higher frequencies than millimeter waves, especially in the terahertz and infrared regions, possibly due to the lack of low-loss waveguides, a sharp metal tip is widely used as a scanning probe. 23,[25][26][27][28][29][30][31][32][33][34][35] In this microscopy format, the metal tip is held close to the surface of the sample and evanescent waves are converted to propagating waves. The radiation scattered from the incident radiation is measured for imaging.…”
Section: Introductionmentioning
confidence: 99%